Interferon-gamma alters the phagocytic activity of the mouse trophoblast - Abrahamsohn Ises; Leanza Eduardo C; Gagioti Sonia M; Hoshida Mara S; Albieri Andréa; Croy Anne; Ashkar Ali A; Bevilacqua Estela (BMC, 2005)
Abstract Interferon-gamma (IFN-gamma) mediates diverse functions in bone marrow-derived phagocytes, including phagocytosis and microbe destruction. This cytokine has also been detected at implantation sites under both physiological and pathological conditions in many different species. At these particular sites, the outermost embryonic cell layer in close contact with the maternal tissues, the trophoblast exhibits intense phagocytic activity. To determine whether IFN-gamma affects phagocytosis of mouse-trophoblast cells, ectoplacental cone-derived trophoblast was cultured and evaluated for erythrophagocytosis. Phagocytic activity was monitored ultrastructurally and expressed as percentage of phagocytic trophoblast in total trophoblast cells. Conditioned medium from concanavalin-A-stimulated spleen cells significantly enhanced trophoblast phagocytosis. This effect was blocked by pre-incubation with an anti-IFN-gamma neutralizing antibody. Introduction of mouse recombinant IFN-gamma (mrIFN-gamma) to cultures did not increase cell death, but augmented the percentage of phagocytic cells in a dose-dependent manner. Ectoplacental cones from mice deficient for IFN-gamma receptor alpha-chain showed a significant decrease of the phagocytosis, even under mrIFN-gamma stimulation, suggesting that IFN-gamma-induced phagocytosis are receptor-mediated. Reverse transcriptase-PCR analyses confirmed the presence of mRNA for IFN-gamma receptor alpha and beta-chains in trophoblast cells and detected a significant increase in the mRNA levels of IFN-gamma receptor beta-chain, mainly, when cultured cells were exposed to IFN-gamma. Immunohistochemistry and Western blot analyses also revealed protein expression of the IFN-gamma receptor alpha-chain. These results suggest that IFN-gamma may participate in the phagocytic activation of the mouse trophoblast, albeit the exact mechanism was not hereby elucidated. Protective and/or nutritional fetal benefit may result from this physiological response. In addition, our data also shed some light on the understanding of trophoblast tolerance to inflammatory/immune cytokines during normal gestation.